"Not only a matter of personal interest": vaccination narratives and the model of moral motives in China and Germany - Müller, Selina; Wachinger, Jonas; Jiao, Lirui; Bärnighausen, Till; Chen, Simiao; McMahon-Rössle, Shannon A. (Qualitative health research, 2024)
Understanding vaccination decision-making processes is vital for guiding vaccine promotion within pandemic contexts and for routine immunization efforts. Vaccine-related attitudes influencing individual decision-making can be affected by broader cultural and normative contexts. We conducted 73 qualitative interviews with adults in China (n = 40) and Germany (n = 33) between December 2020 and April 2021 to understand COVID-19 vaccination intentions and preferences, and we analyzed transcripts using a five-step framework approach. During early analysis, we identified moral considerations in line with the tenets of the Model of Moral Motives (MMM) as a recurrent theme in the data. The MMM guided further analysis steps, particularly with its distinction between motives that are proscriptive (focus on avoiding harm by inhibiting “bad” behavior) and prescriptive (focus on actively seeking positive outcomes). Proscriptive vaccination arguments that compelled vaccination in our data included avoiding negative attention, being a law-abiding citizen, preventing harm to others, and protecting one’s country. Prescriptive motives focused on self-efficacious behavior such as protecting the health of oneself and others via widespread but voluntary vaccination, prioritizing elderly and predisposed individuals for vaccination, and favoring a fair and equitable distribution of vaccines at the global level. In the interviews in China, both lines of arguments emerged, with a general tendency toward more proscriptive reasoning; interviews conducted in Germany tended to reflect more prescriptive motives. We encourage research and vaccine promotion practice to reflect moral considerations when aiming to understand public health preventive behavior and when developing tailored health promotion campaigns.